The influence of human resources management practice on employee performance at the National Land Agency Province of North Sumatra - Saima Rambe (Institute of Computer Science (IOCS), 2022)
This research is to determine directly how far human resource management practices affect employee performance in the Administration section of the National Land Agency for North Sumatra Province. The population and sample in this study were all employees of the Administrative Section of the National Land Agency, totaling 35 employees. The lack of implementation of the management and supervision of human resources so the lack of discipline in administrative employees in their duties and responsibilities results in the quality of human resources not achieving the level of performance as desired. Human Resources on Employee Performance of the Medan National Land Agency. The purpose of this study was to determine the extent to which the influence of human resource management practices on employee performance at the Administrative Section of the Regional Office of the National Land Agency of North Sumatra Province. The research method used is a quantitative research method using the product moment formula with 2 variables, namely X and Y. From the conclusion of the research results that variable (X) and variable (Y) are at a Strong level, it is proven that the result of calculating the product-moment correlation is between 0 .60 - 0.79 which indicates a strong interpretation of the National Land Agency. And the results of the calculation of the t-test as seen above can be obtained by the value of tcount = 7.414 the number of moment products contained in the ttable with (df) 0.05% at n = 35 there is a number of ttable = 2.034. This means that with the number 7.414 > 2.034, the hypothesis submitted can be accepted at the Office of the National Land Agency for the Province of North Sumatra.